Association between a genetic index for lameness resistance and the incidence of claw horn lesions in Holstein cows. (25th April 2022) - Barden, Matthew; Anagnostopoulos, Alkiviadis; Griffiths, Bethany E.; Bedford, Cherril; Winters, Marco; Li, Bingjie; Coffey, Mike; Psifidi, Androniki; Banos, Georgios; Oikonomou, Georgios
Abstract: Background: This study aimed to determine the association between the lameness advantage genetic index and four outcomes: sole haemorrhage (SH), sole ulcers (SU), white line lesions (WL), and lameness during mobility scoring. Methods: We enrolled 2352 Holstein cows from four predominantly housed dairy herds in the UK. Cows were mobility scored and foot lesions recorded at four time points from before calving to late lactation. Cows were genotyped and genetic indexes were assigned to each cow following national genetic evaluations. Lameness records and genetic indexes were matched for 2107 cows. Four separate multivariable logistic regression models, which included farm and parity as covariables, were used to quantify the association between the lameness advantage index and whether animals were affected by SH, SU, WL, or lameness. Results: The odds ratios (95% confidence intervals) for one‐point increases in the lameness advantage index were 0.79 (0.72–0.86), 0.68 (0.59–0.78), 0.94 (0.84–1.04), and 0.82 (0.74–0.91) for SH, SU, WL, and lameness, respectively. The same trends were present when the sire's lameness advantage index was evaluated in place of the animal's own, although the strength of this association was generally weaker. Conclusion: The lameness advantage index is associated with SH, SU, and lameness, therefore selection on the lameness advantage index could be considered in herds aiming to reduce lameness. Where genomic testing of heifers is not conducted, sire lameness advantage index may still be effective to reduce SH and SU incidence.